2023
DOI: 10.1093/cid/ciad450
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Misleading Conclusions in Observational Studies of Time-to-Antibiotics and Mortality in Suspected Sepsis

Abstract: Background Influential studies conclude that each hour until antibiotics increases mortality in sepsis. However, these analyses often 1) adjusted for limited covariates, 2) included patients with long delays until antibiotics, 3) combined sepsis and septic shock, and 4) used linear models presuming each hour delay has equal impact. We evaluated the effect of these analytic choices on associations between time-to-antibiotics and mortality. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Another block-randomized controlled trial assessing the impact of pre-hospital antibiotic administration in patients that met SIRS criteria was unable to show a difference in outcomes based on antibiotic timing. In addition, when conducting observational studies using clinical data, the association between antibiotic timing and outcomes can be significantly impacted by time windows, variables, and definitions used to model the relationship, as a recent study by Pak et al has shown 4. Our study demonstrated that, by evaluating suspected septic shock based on antibiotic timing in relation to hypotension onset (instead of ED presentation time), there was significant heterogeneity in sep-sis presentation and treatment timing.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…Another block-randomized controlled trial assessing the impact of pre-hospital antibiotic administration in patients that met SIRS criteria was unable to show a difference in outcomes based on antibiotic timing. In addition, when conducting observational studies using clinical data, the association between antibiotic timing and outcomes can be significantly impacted by time windows, variables, and definitions used to model the relationship, as a recent study by Pak et al has shown 4. Our study demonstrated that, by evaluating suspected septic shock based on antibiotic timing in relation to hypotension onset (instead of ED presentation time), there was significant heterogeneity in sep-sis presentation and treatment timing.…”
mentioning
confidence: 78%
“… 14 The study was limited to patients with “suspected septic shock,” defined as a systolic blood pressure (SBP) less than 90 mmHg within 24 h of ED presentation, similar to a recently published article by Pak et al. 4 We excluded those with resolution of hypotension within 30 min of its start to eliminate spurious hypotension. Repeat encounters were treated independently.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2023 retrospective study examining 104,248 patients revealed that every hour delay in administering antibiotics correlated with a heightened risk of mortality from septic shock. However, for non-shock patients, delays > 6 h correlate with higher mortality [21]. Inappropriate antibiotic therapy in patients with septic shock is associated with a signi cant increase in mortality.…”
Section: Etiology and Treatment Of Sepsismentioning
confidence: 99%